Nature and Nurture in Mental Disorders A Gene-Environment Model. - Paris, Joel (American Psychiatric Publishing, 2020)
The book thoughtfully discusses the theories that affect the study of genes, the environment, and their interaction and examines what the empirical evidence reveals about each of these issues. The author posits a biopsychosocial approach -- one that acknowledges the role an individual's predisposing genetic factors, interacting with environmental stressors, play in the etiology of many mental disorders.